Effectiveness and practicality of control strategies for African swine fever: what do we really know?. (28th January 2017) - Guinat, C.; Vergne, T.; Jurado‐Diaz, C.; Sánchez‐Vizcaíno, J. M.; Dixon, L.; Pfeiffer, D. U.
Abstract : African swine fever (ASF) is a major pig health problem, and the causative virus is moving closer to Western European regions where pig density is high. Stopping or slowing down the spread of ASF requires mitigation strategies that are both effective and practical. Based on the elicitation of ASF expert opinion, this study identified surveillance and intervention strategies for ASF that are perceived as the most effective by providing the best combination between effectiveness and practicality. Among the 20 surveillance strategies that were identified, passive surveillance of wild boar and syndromic surveillance of pig mortality were considered to be the most effective surveillance strategies for controlling ASF virus spread. Among the 22 intervention strategies that were identified, culling of all infected herds and movement bans for neighbouring herds were regarded as the most effective intervention strategies. Active surveillance and carcase removal in wild boar populations were rated as the most effective surveillance and intervention strategies, but were also considered to be the least practical, suggesting that more research is needed to develop more effective methods for controlling ASF in wild boar populations.